Explaining the spatial heterogeneity in soil–rice yield interactions via a hybrid interpretable machine learning and spatial analysis framework - Meiling Sheng; Xufeng Fei; Zhaohan Lou; Mingtao Xiang; Zhouqiao Ren; Xiaonan Lv; Rui Xiao (Journal of Environmental Management, 2026)

Multifunctional metallized basalt/PA6 composites: EMI shielding, joule heating, and tunable rigidity - Jiajun Du; Hao Shi; Xin Wang; Meiling Xiang; Jing Zhang (Chemical Engineering Journal, 2026)

Analysis of the spatiotemporal evolution and determinants of cultivated land quality under a hybrid-driven framework integrating multiple machine learning and geostatistical approaches - Meiling Sheng; Zhaohan Lou; Mingtao Xiang; Rui Xiao; Zhouqiao Ren; Xiaonan Lv; Xufeng Fei (Stochastic Environmental Research and Risk Assessment, 2026)

Development and validation of a copolymerized thiol-silica based DGT technique for the assessment of bioavailable As(Ⅲ) speciation - Yue Zeng; Zhennan Liu; Yajie Jiang; Yunqin Li; Wei Yu; Rong Yu; Xiang Xu; Meiling Xiao (Environmental Geochemistry and Health, 2026)

Spatiotemporal changes of soil organic carbon in intensive croplands over three decades: Emerging role of farmland utilization shifts - Mingtao Xiang; Xiaojia Chen; Songchao Chen; Chunyan Wu; Meiling Sheng; Zhouqiao Ren; Wanzhu Ma; Ming Ming; Xunfei Deng; Yu Zhan (Soil and Tillage Research, 2025)

Long non-coding RNA profiling reveals lncRNA MslncLOX13S that promotes lipoxygenase gene expression and enhances the tolerance to selenium in Medicago sativa L. - Qingdong Wang; Mengli Xu; Meiling Xiang; Yarui Sheng; Huafeng Hu; Tianyu Zhang (Journal of Plant Physiology, 2025)

Estimating the spatial distribution and exploring the factors influencing cultivated land quality through a hybrid random forest and Bayesian maximum entropy model - Xufeng Fei; Zhaohan Lou; Meiling Sheng; Mingtao Xiang; Rui Xiao; Zhouqiao Ren; Xiaonan Lv (Environmental Research, 2025)

Regulatory mechanism of microplastics on arsenic bioavailability in a subtropical estuary, China - Yue Zeng; Yajie Jiang; Yunqin Li; Xiang Xu; Rong Yu; Wei Yu; Binxin Wu; Meiling Xiao (Science of The Total Environment, 2025)

Self-assembled mogroside v nanomicelle system improves oral bioavailability of the magnolol - Chengzhi Liu; Lingyi Ren; Niu Liu; Mengchu Niu; Yifei Xiang; Xianhua Wu; Changhua Lin; Zhengmin Liang; Meiling Yu; Jiakang He (Food Chemistry, 2025)

Exploring the spatio-temporal dynamics and driving mechanisms of toxic metal pollution in soil using a hybrid machine learning-based model - Mingtao Xiang; Zhaohan Lou; Meiling Sheng; Zhouqiao Ren; Rui Xiao; Xufeng Fei; Xiaonan Lv (Journal of Environmental Chemical Engineering, 2025)

Microscale fluvial landscape evolution and its impacts on early human settlement at the Shangshan cultural site in the upper Qiantang region, eastern China - Wenjia Zhang; Zhou Lin; Guoping Zhang; Leping Jiang; Meiling Chen; Shengchao Zhou; Yuchen Zhang; Xiang Zhao (Geomorphology, 2025)

Thresholding Dolphin Whistles Based on Signal Correlation and Impulsive Noise Features Under Stationary Wavelet Transform - Xiang Zhou; Ru Wu; Wen Chen; Meiling Dai; Peibin Zhu; Xiaomei Xu (Journal of Marine Science and Engineering, 2025)
The time–frequency characteristics of dolphin whistle signals under diverse ecological conditions and during environmental changes are key research topics that focus on the adaptive and response mechanisms of dolphins to the marine environment. To enhance the quality and utilization of passive acoustic monitoring (PAM) recorded dolphin whistles, the challenges faced by current wavelet thresholding methods in achieving precise threshold denoising under low signal-to-noise ratio (SNR) are confronted. This paper presents a thresholding denoising method based on stationary wavelet transform (SWT), utilizing suppression impulsive and autocorrelation function (SI-ACF) to select precise thresholds. This method introduces a denoising metric ρ, based on the correlation of whistle signals, which facilitates precise threshold estimation under low SNR without requiring prior information. Additionally, it exploits the high amplitude and broadband characteristics of impulsive noise, and utilizes the multi-resolution information of the wavelet domain to remove impulsive noise through a multi-level sliding window approach. The SI-ACF method was validated using both simulated and real whistle datasets. Simulated signals were employed to evaluate the method’s denoising performance under three types of typical underwater noise. Real whistles were used to confirm its applicability in real scenarios. The test results show the SI-ACF method effectively eliminates noise, improves whistle signal spectrogram visualization, and enhances the accuracy of automated whistle detection, highlighting its potential for whistle signal preprocessing under low SNR.

Occupation patterns during the Shangshan in the upper Qiantang River Basin, eastern China: A geomorphic study based on GIS - Wenjia Zhang; Zhou Lin; Leping Jiang; Chao Ding; Meiling Chen; Shengchao Zhou; Xiang Zhao (Quaternary International, 2024)

Evaluation of magnetic calcium silicate hydrate derived from halloysite clay for efficient phosphate capture - Debin Jiang; Xue Long; Meiling Xiang; Xiantian Gan; Qinghong Pu; Yu Chen; Ning Qi; Xiaoping Wang (Journal of Environmental Chemical Engineering, 2024)

Topological analysis, endogenous mechanisms, and supply risk propagation in the polycrystalline silicon trade dependency network - Chaohao miao; Yanfang wan; Meiling kang; Fu Xiang (Journal of Cleaner Production, 2024)

High mechanical CuO@stainless steel mesh for continuous and durable separation of surfactant-stabilized viscous and light/heavy-mixed oily emulsions in liter-scale - Qing He; Meiling Guo; Juan Shu; Hua Hu; Hongwei Su; Guilong Yan; Zhenyu Li; Li Wang; Dong Xiang; Chunxia Zhao; Yuanpeng Wu; Wei Wang; et al. (Journal of Water Process Engineering, 2023)

Elevated CO2 alleviated the dissemination of antibiotic resistance genes in sulfadiazine-contaminated soil: A free-air CO2 enrichment study - Meiling Xu; Qian Xiang; Fen Xu; Lei Guo; Laura J. Carter; Wenchao Du; Chunwu Zhu; Ying Yin; Rong Ji; Xiaozhi Wang; Hongyan Guo (Journal of Hazardous Materials, 2023)

High-throughput sequencing reveals tuber mustard genes responsive to Plasmodiophora brassicae in the early stage of infection - Zhaoming Cai; Meiqin Xiang; Jing Tan; Chunhong Cheng; Ying Liu; Jiayu Shi; Meiling Shi; Jin Li; Diandong Wang (Physiological and Molecular Plant Pathology, 2023)

Integrated eco-physiological, biochemical, and molecular biological analyses of selenium fortification mechanism in alfalfa - Qingdong Wang; Jinke Hu; Huafeng Hu; Yan Li; Meiling Xiang; Dezhen Wang (Planta, 2022)

Autonomous selfing is altered by pollination in delayed-selfing species Gentianopsis paludosa (Gentianaceae) - Qinzheng Hou; Xiang Zhao; Meiling Duan; Yiping Zhang (Brazilian Journal of Botany, 2022)

Comparative transcriptome analysis of global effect of ddh and lysE deletion on 4-hydroxyisoleucine production in Corynebacterium glutamicum - Rui Chen; Youhe Xiang; Xinping Yu; Meiling Zhang; Feng Shi (Systems Microbiology and Biomanufacturing, 2022)

Integrating Genome-Wide Association Study and Brain Expression Data Highlights Cell Adhesion Molecules and Purine Metabolism in Alzheimer’s Disease - Zimin Xiang; Meiling Xu; Mingzhi Liao; Yongshuai Jiang; Qinghua Jiang; Rennan Feng; Liangcai Zhang; Guoda Ma; Guangyu Wang; Zugen Chen; Bin Zhao; Tiansheng Sun; et al. (Molecular Neurobiology, 2015)

Allosteric therapies for lung cancer - Ye Ling; Meiling Jing; Xiang-dong Wang (Cancer and Metastasis Reviews, 2015)

An asexual Epichloë endophyte modifies the nutrient stoichiometry of wild barley (Hordeum brevisubulatum) under salt stress - Meiling Song; Qing Chai; Xiuzhang Li; Xiang Yao; Chunjie Li; Michael J. Christensen; Zhibiao Nan (Plant and Soil, 2015)